SIGHT TRANSLATION TEACHING METHODS USED BY LECTURERS AT TRANSLATOR AND INTERPRETER TRAINING DIVISION, FACULTY OF ENGLISH LANGUAGE TEACHER EDUCATION, UNIVERSITY OF LANGUAGES AND INTERNATIONAL STUDIES, VIETNAM NATIONAL UNIVERSITY AND THOSE AT ENGLISH DEPARTMENT, HANOI UNIVERSITY = Các phương pháp giảng dạy dịch đọc được các giáo viên ngành Biên phiên dịch, khoa Sư phạm tiếng Anh, trường Đại học ngoại ngữ, ĐHQGHN và các giáo viên khoa tiếng Anh, trường Đại học Hà Nội sử dụng - Đỗ, Thu Hoài (2020)
Translation and interpretation have been taught in a lot of universities in Vietnam for many recent years. In the curriculums for translation and interpretation of the Translation and Interpretation Division, English Teacher Education Department in the University of Languages and International Studies, Vietnam National University and the English Department, Hanoi University, sight translation is introduced via different forms. As one of the first studies on sight translation teaching, this paper aimed at investigating different types of sight translation exercises applied to teach students of translation and interpretation major in the two universities. In order to achieve this goal, the research used questionnaires and interviews to collect data. Questionnaires were delivered to 132 students in ULIS and HANU. Interviews were conducted with six lecturers from both universities. Through data collection and analysis, eight different types of sight translation exercises used by lecturers in ULIS and HANU were identified. The results show that the number of exercise types used in ULIS is larger than that used in HANU. In addition, lecturers in Translation and Interpretation Division of ULIS tend to design more detailed and complex exercises for their students than those in English Department, HANU. Because they are taught different exercise types, students in the two universities also have different evaluation on the most effective type for them. As this is the first research on sight translation teaching in ULIS and HANU, there are some limitations, which gives opportunity for further researches in the futures. Some recommendations are given in the last chapter of the paper.